Cancer Profile in East Jakarta: A 5-year descriptive study - Gondhowiardjo, Soehartati Argadikoesoema; Hanum, Fathiya Juwita; Hanifah, Rizka; Priharto, R Koesmedi; Yekti, Widyastuti Endro (Radioterapi & Onkologi Indonesia, 2018)
Background: Global Burden of Cancer (GLOBOCAN) 2012 estimated there were 8.2 million cancer deaths worldwide, 65% of them were in developing countries. In Indonesia, the cancer incidence is 134 per 100,000 population. The magnitude of the burden caused by cancer requires a valid data collection in each country in an effort to plan and evaluate cancer prevention programs in the future. Based on Indonesian Minister of health decree, Dr. Cipto Mangunkusumo Hospital (RSCM) was determined as Cancer Registry Control Center in DKI Jakarta Province. This study aims to report Cancer Profile in East Jakarta 2008-2012 based on RSCM Data.Methods: This research was a cross-sectional descriptive study. Patient data were extracted from DKI Jakarta Cancer Registry Control Center Located at RSCM. The primary site and histology of malignancies were identified and coded based on the International Classification of Diseases for Oncology.Results: There were 3748 cancer patients who live in East Jakarta, with male and female ratio of 1:1.9. Most of them were between 45-54 years old. The majority of patients came to health providers with advanced stage (stage 3 and 4). At both sexes the most frequent cancer were breast cancer, followed by cervical cancer, hematopoietic and reticuloendothelial system malignancy, nasopharyngeal cancer, and lung and bronchial cancer. The five most common cancers in men were nasopharyngeal cancer, hematopoietic and reticuloendothelial system malignancy, lung and bronchial cancer, liver and intrahepatic bile duct cancer, and lymph node cancer, respectively. While in women, the five most common cancers were breast cancer, cervical cancer, ovarian cancer, hematopoietic and reticuloendothelial system malignancy and thyroid gland cancer, respectively.Conclusion: Most of cancer patients are in productive age and the majority of them came at advanced stage. Furthermore, three of five most common cancer charge both genders (hematopoietic and reticuloendothelial system malignancy, nasopharyngeal cancer, and lung and bronchial cancer).